(U-Th)/He thermochronometry constraints on the Mesozoic-Cenozoic tectono-thermal evolution of Kuqa basin: A case study of well TZ2 - Yu, S.; Chen, W.; Lü, X.; Evans, Noreen; McInnes, Brent; Yin, J.; Sun, J. (Wiley Blackwelll Publishing, 2014)
The oil and gas resources in Kuqa foreland basin are rich, however, there is a lack of effective researches of the tectonic thermal history in the Mesozoic and Cenozoic period, which is important for oil and gas exploration. Based on the tested apatite and zircon He ages data from drilling well samples, the He closure temperature of borehole apatites from Kuqa basin is determined (about 89?) by analyzing the relationship between apatite ages of (U-Th)/He and depth/temperature in profile. Mesozoic-Cenozoic thermal history of the well TZ2 will has been modeled by using the He ages and vitrinite reflectance (Ro) data. The modeling result shows that the forming time of Tuziluoke anticline started at 5 Ma, and it uplifted and eroded about 670 m in Cenozoic period with the average erosion rate of 0.133 mm/a. According to structural evolution analysis of Tuziluoke anticline, the time of gas-migrating fault activity and trap formation was determined, which demonstrated the time of gas accumulation in the Tuziluoke anticline was 5 Ma. The consistency of the times of the hydrocarbon generation and expulsion, fault activity and trap formation was key factor for gas accumulation in Tuziluoke anticline. Therefore, application of the (U-Th)/He technology to the tectono-thermal evolution of sedimentary basin has the important significance for oil and gas exploration in Kuqa basin.